2021
DOI: 10.1108/nbri-12-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between social media and social networks in marketing research: a bibliometric view

Abstract: Purpose This paper aims to systematically find the main research differences and similarities between social media and social networks in marketing research using the bibliometric perspective and provides suggestions for firms to improve their marketing strategies effectively. Design/methodology/approach The methods of co-word analysis and network analysis have been used to analyze the two research fields of social media and social networks. Specifically, this study selects 2,424 articles from 27 marketing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 113 publications
(181 reference statements)
0
3
0
Order By: Relevance
“…This phenomenon represents an emerging marketing model (Putri and Ernawaty, 2020;Salehi et al, 2012). The study conducted by Zhao et al (2021) found that social media offers various practical implications and recommendations on how companies can enhance their utilization of social media and social networks for marketing purposes. From an economic standpoint, the analysis of current marketing research suggests that consumercentric strategies in social media and social network marketing consistently yield positive effects on business performance.…”
Section: Social Media Influencermentioning
confidence: 99%
“…This phenomenon represents an emerging marketing model (Putri and Ernawaty, 2020;Salehi et al, 2012). The study conducted by Zhao et al (2021) found that social media offers various practical implications and recommendations on how companies can enhance their utilization of social media and social networks for marketing purposes. From an economic standpoint, the analysis of current marketing research suggests that consumercentric strategies in social media and social network marketing consistently yield positive effects on business performance.…”
Section: Social Media Influencermentioning
confidence: 99%
“…The fact that anyone can receive live news through social media about anything around the globe has made many people more aware and educated on political issues. This is the time to remember what a social network is and from which parts are defined (Hong Zhao, 2021) [11] . It is a means through which the person maintains his social identity, receives emotional or ~ 276 ~ material support, participates in services, has access to information, and creates new social contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Wang (2021) social networks and social media are both research hotspots within the discipline of marketing research.…”
mentioning
confidence: 99%